Methods of developing the choreographic vocabulary of competitive variations of Latin American dances - Hamivka, Albina; Бугаєць, Наталія; Pinchuk, Olga (Professional Art Education, 2024)
The article reveals the methods of developing the choreographic vocabulary of competition variations of Latin American dances. The content and specific features of Latin American dances as one of the types of sports ballroom dances are clarified. Methods & methodology: method of analysis and synthesis for processing and systematization scientific information; method of terminological analysis to reveal the essence basic concepts; an activity method for identifying artistic methods of development vocabulary of competitive variations of the Pasodoble dance; historical approach to find out evolution of the use of the concept of «variation» in choreography. The scientific novelty the essence of the main concepts was specified and specified: «the discipline of Pro-Am», «Pasodoble dance», «competition variation of the Pasodoble dance», «artistic methods of vocabulary development of competition variations». Results. Sports dance, in particular its constituent part - Latin American dance, is a multi-faceted and multi-component sport that integrates such areas as performative, plastic, coordination and sports. They are distinguished by the variety of different movements and positions in a pair and are also accompanied by a melody that contributes to the formation of the figurative content of these dances, which is embodied through the use of various choreographic techniques. Conclusions. Sports dance, in particular its constituent part - Latin American dance, is a multifaceted and multi-component sport that integrates such areas as performative, plastic, coordination and sports. They are distinguished by the variety of different movements and positions in a pair and are also accompanied by a melody that contributes to the formation of the figurative content of these dances, which is embodied through the use of various choreographic techniques.